Increased targeted HIV testing and reduced undiagnosed HIV infections among gay and bisexual men. Issue 7 (19th April 2021) - Patel, PG; Keen, P; McManus, H; Duck, T; Callander, D; Selvey, C; Power, C; Gray, RT; Knight, V; Asselin, J; Read, P; Johnson, K; et al.
Abstract : Objectives: To evaluate the impact of government HIV strategies that aimed to increase HIV testing uptake and frequency among gay and bisexual men (GBM) in New South Wales (NSW), Australia. Design: We analysed HIV testing data from existing passive and sentinel surveillance systems between 2010 and 2018. Methods: Six indicators were measured: (1) state‐wide total HIV laboratory tests; (2) number of GBM attending publicly‐funded clinics; (3) 12‐monthly testing uptake; (4) annual testing frequency; (5) HIV testing with a STI diagnosis; and (6) HIV positivity. Mathematical modelling was used to estimate (7) the proportion of men with undiagnosed HIV. Indicators were stratified by Australian vs. overseas‐born. Results: Overall, 43, 560 GBM attended participating clinics (22, 662 Australian‐born, 20, 834 overseas‐born) from 2010‐2018. Attendees increased from 5, 186 in 2010 to 16, 507 in 2018. There were increasing trends (p<0.001 for all) in testing uptake (83.9% to 95.1%); testing with a STI diagnosis (68.7% to 94.0%); annual HIV testing frequency (1.4 to 2.7); and a decreasing trend (p<0.01) in HIV positivity (1.7% to 0.9%).Increases in testing were similar in Australian‐born and overseas‐born GBM. However, there were decreasing trends in the estimated undiagnosed HIV proportion overall (9.5% to 7.7%) and in Australian‐born GBM (7.1% to 2.8%), but an increasing trend in overseas‐born GBM (15.3% to 16.9%) (p<0.001 for all).